PERSEPSI MAHASISWA DALAM PERKULIAHAN DARING PADA MATA KULIAH BAHASA INDONESIA DI UNIVERSITAS AMIKOM YOGYAKARTA - Anggit Tiyas Fitra Romadani; Yusi Kurniati (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2023)
This study aims to describe student perceptions of the implementation of online lectures in the Indonesian language course at Amikom University, Yogyakarta. The results of the study show that most students have a positive perception of the implementation of online lectures in Indonesian courses. This perception is measured from three aspects, including aspects of the lecture process, aspects of lecturer competence, and aspects of facilities. In the aspect of the lecture process, most students gave a positive perception of the online lecture process. Students think that online lectures can train for independent learning and save on transportation costs. In terms of lecturer competence, most students agree that lecturers are competent so that online lectures can run smoothly. Meanwhile the aspect of facilities, some students stated that facilities in the form of internet networks could be an obstacle in online lectures. However, students always get positive support from parents in online lectures